Characterization and antibacterial activity of biosynthesized silver nanoparticles using Stachytarpheta jamaicensis leaf extract as bioreduction - Sandy Samsul Bahry; Ari Susilowati; Artini Pangastuti (Universitas Gadjah Mada, 2025)
Their nanometer size, broad spectrum, and antibacterial mechanism give silver nanoparticles (NPAg) the potential to be used to inhibit the growth and spread of methicillin‐resistant Staphylococcus aureus (MSRA) in medical devices. Synthesis of AgNPs from Stachytarpheta jamaicensis leaf extract is considered more environmentally friendly and has low production costs. The objective of this study was to investigate the properties and antibacterial potential of AgNPs by utilizing S. jamaicensis leaf extract at concentrations of 0.5%, 1.0%, and 1.5% in a 1 mM AgNO3 precursor. Nanoparticle characterization was performed on the AgNP supernatant obtained by centrifuging the synthesis solution at 100 rpm for 5 min. Characterization of the NPAg size was confirmed by surface plasmon resonance (SPR) analysis in UV‐Vis spectrophotometer, while the size distribution was measured by a particle size analyzer. Surface morphology was performed using scanning electron microscopy (SEM), and antibacterial activity was evaluated by the disc diffusion method. The results showed that AgNPs had the best nanoparticle characteristics in an extract concentration of 0.5%, the synthesis indicated by SPR at a wavelength of 434 nm and an average size of 80.67 nm. SEM analysis showed the formation of clusters at variations of 1.0% and 1.5%. The antibacterial activity of AgNPs against MRSA was the highest at 0.5%, with an inhibition zone diameter of 0.77 mm. The higher concentration of S. jamaicencis leaf extract increases the risk of cluster formation, which enlarges the AgNPs, while antibacterial activity was reduced.